2020
DOI: 10.1017/s1479262120000222
|View full text |Cite
|
Sign up to set email alerts
|

QTL mapping for stripe rust and powdery mildew resistance in Triticum durumAegilops speltoides backcross introgression lines

Abstract: Wheat, a major food crop, faces significant yield constraints due to losses caused by various diseases, especially rusts and powdery mildew. Since the causal organisms are always evolving, there is a never-ending hunt for new genes/quantitative trait loci (QTLs) for resistance to control the damage. For this purpose, Triticum durum–Aegilops speltoides backcross introgression lines (DS-BILs) developed in our wide hybridization programme were screened against stripe rust and powdery mildew at both seedling and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…In the present study, the FarmCPU algorithm identified eight significant MTAs associated with stripe rust on chromosomes 2A, 2D, 5B, 6A, and 7A. Q.Yr.bisa-2A.3 on chromosome 2A at the physical position 753.3 Mb identified for YR resistance in this study was found in the vicinity of a Q.YrTd.pau.2A.2 mapped at 766.16 Mb by Dhillon et al (2020) . Another QTL mapped on chr2D ( Q.Yr.bisa-2D ) at a terminal end of 2DS was identified in the vicinity (∼70 Mb apart) of QYr.caas-2DS_Libellula ( Lu et al, 2009 ).…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…In the present study, the FarmCPU algorithm identified eight significant MTAs associated with stripe rust on chromosomes 2A, 2D, 5B, 6A, and 7A. Q.Yr.bisa-2A.3 on chromosome 2A at the physical position 753.3 Mb identified for YR resistance in this study was found in the vicinity of a Q.YrTd.pau.2A.2 mapped at 766.16 Mb by Dhillon et al (2020) . Another QTL mapped on chr2D ( Q.Yr.bisa-2D ) at a terminal end of 2DS was identified in the vicinity (∼70 Mb apart) of QYr.caas-2DS_Libellula ( Lu et al, 2009 ).…”
Section: Discussionsupporting
confidence: 49%
“…their possible functional roles in disease resistance. The genes identified were directly or indirectly involved in pathogenesis or plant-pathogen interaction ( Dhillon et al (2020). Another QTL mapped on chr2D (Q.Yr.bisa-2D) at a terminal end of 2DS was identified in the vicinity (∼70 Mb apart) of QYr.caas-2DS_Libellula (Lu et al, 2009).…”
Section: Candidate Resistance-associated Loci Identified By Genome-wide Association Studymentioning
confidence: 99%
“…To counter the constraints from foliar diseases like SB, there is a need for constantly identifying and introgressing new sources of resistance. The DSBIL panel used in the present study showed wide range of variation for different traits and has already been reported to possess various QTLs for heat tolerance, stripe rust, and powdery mildew resistance (Awlachew et al, 2016;Dhillon et al, 2020). In the present study, during phenotypic evaluation of disease severity for SB, three DSBILs (DSBIL 13, 61, and 80) were identified to be highly resistant against SB.…”
Section: Discussionmentioning
confidence: 69%
“…Global climate change and ever-evolving pathogens are major causes of the reduction in crop production (Meehl and Tebaldi, 2004; Bebber et al ., 2013; Hua, 2013; Velásquez et al ., 2018; Dhillon et al ., 2020; Arora et al ., 2021). Temperature and rainfall fluctuations play a critical role in hindering successful crop cultivation (Dixon, 2012; Fischer and Knutti, 2015; Hatfield and Prueger, 2015; Dubey et al ., 2019, 2020; Sattar et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%